The Importance Of Education To Understand Trade Facilitation Agreement (TFA) - Jati, Kumara; Mardiansyah, Arie; Fawaiq, Muhammad; Ingot, Steven Raja (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2019)
Education is a very essential factor in human life, because if someone get the certain knowledge then they will be able to make a better decision, self empowerment and aware of rules and regulations in the world. Two of the important regulations related to international trade are coming from The World Trade Organization (WTO) and Trade Facilitation Agreement (TFA). Indonesia has ratified the Trade Facilitation Agreement (TFA) on 5 December 2017. The new agreement related to WTO and TFA needed to be learnt and teach with a good Education Model. The most important role of skill policies and education in globalization era is its role in facilitating the international flow of ideas. This research can fill the gap to make an Educational Model of TFA based on Non-Juridical and Juridical Education. Both factors become very important things because the stakeholders can use this model to more quickly and easily understand the substance of TFA, so that Indonesia can fully implement the TFA commitments in the digital database WTO in the year 2022.